Appropriateness of Antibiotic Prescribing in US Emergency Department Visits, 2016-2021 - Joseph Benigno Ladines-Lim; Michael A. Fischer; Jeffrey A. Linder; Kao-Ping Chua (Cambridge University Press, 2024)
In this national analysis of US emergency department visits with antibiotic prescribing during 2016-2021, 27.6% of visits resulted in inappropriate antibiotic prescribing: 14.9% had diagnosis codes plausibly antibiotic-related (eg, acute bronchitis), suggesting actual inappropriate prescribing, and 12.6% had diagnosis codes not plausibly antibiotic-related (eg, hypertension), suggesting poor coding quality.